The Influence of Master of Management Studies and Work Experience on Workplace Decision-Making Ability: The Mediating Role of Self-Efficacy - Muhammad Abiyyu Akmal; Osly Usman (Journal of Digital Business and Global Economy, 2026)
This study examines the influence of Master of Management (MM) studies and work experience on workplace decision-making ability, with self-efficacy as a mediating variable. A VOSviewer bibliometric analysis of 30 Scopus-indexed journals identified that this integrated model remains underexplored in management contexts, particularly in publications after 2020. A quantitative approach was employed with data collected from 98 respondents active MM students or graduates currently employed via an online questionnaire. Hypotheses were tested using PLS-SEM with SmartPLS 4 (SRMR = 0.077). Results indicate that MM studies significantly influence self-efficacy (β = 0.269, p = 0.008), and work experience significantly influences both self-efficacy (β = 0.535, p < 0.001) and workplace decision-making directly (β = 0.518, p < 0.001). However, self-efficacy did not significantly mediate either relationship, and MM studies showed no direct effect on decision-making. These findings suggest that practical work experience is a more immediate driver of self-efficacy and decision-making capacity than formal postgraduate education, especially when studies are still in progress. Future research should replicate this study with larger samples of MM graduates and longitudinal designs to more definitively assess the mediating role of self-efficacy.